Balik Nama Sertifikat Tanah Tanpa Adanya Akta Jual Beli - Nur Sa’adah (Rechtsregel : Jurnal Ilmu Hukum, 2021)
The purpose of this study is to find out the transfer of name of the land title without a deed of sale and purchase. This study uses a normative type of research which examines the rule of law, legal principles, legal doctrine and the existing legal system in our country. From this study, the results show that the Letter of Sale and Purchase of land/building is evidence of a legal sale and purchase transaction of land/building as long as there is an agreement between both parties and has fulfilled the legal requirements of the agreement as stipulated in the Civil Code. To transfer the name of a certificate based on a Sale and Purchase Agreement, it can be done on the basis of a decision from the court, in this case no longer through the Deed of Sale and Purchase of land and buildings, but the Law of Land registration regulates that to carry out a transfer of name, there must attach conditions, they are the original certificate, without the original certificate, anyone can't transfer the name, even though the buyer has control of the land/building but can't own it yet.